ECONOMIC ANALYSIS FOR A RISK IN THE CULTIVATION OF WHEAT ON OF HIGH SALINITY SOILS WHICH IN IRAQ, USING THE MODEL (MOTAD) - WASIT GOVORNORATE AN APPLIED MODEL - & Farhan, Nassir (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Agriculture is a biological industry with highly vulnerable to natural factors, so the cultivation of wheat crop is very risky in lands, characterized by high levels of soil salinity, leading to high risk and uncertainty component. For this Al-MOTAD model has been adopted to analysis the risk. The research depends on a random sample composed of 590 farmers, representing eight agricultural sectors from agricultural cultivation Wasit Directorate. The Basic Plan for linear programming been designed , and then built al MOTAD model for risk, after nine plans to al MOTAD model represent different levels of degrees of risk posed by the average total absolute deviations A, with levels of income E, until it reached the degree of risk to a minimum as possible in results of ninth Plan to zero level for degrees of risk with the level of net return of 39028220 dinars, cultivation 260578 donnum, and 145560 donnum, and 122748 donnum, and 83611.7 donnum of wheat in different levels of the soil which does not exceed the salinity 8 ds m-1. And cultivating 10428 donnum of industrial barley , and 137663.3 donnum of Gath, and 2422.8 donnum maize in the land that salinity level higher than 8 ds m-1.